Laparoscopic Adrenalectomy: Preventive Principles in Intra- and Postoperative Complications - S. P. Muzhikov; M. Iu. Eremenko; A. G. Baryshev (Креативная хирургия и онкология)
Background. Laparoscopic adrenalectomy is the current surgery of choice in most adrenal tumours, with a nearly 11 % complication rate and below 1 % mortality. Laparoscopy combines the advantages of minimally invasive surgery with well-known long-term prognosis of a traditional open surgery, at the same time requiring the surgeon’s skill of knowing the technique and avoiding complication.Aim. Concept definition of safe laparoscopic adrenalectomy.Materials and methods. A total of 28 patients with adrenal neoplasms were rendered laparoscopic adrenalectomy by same surgical team under benchmark recommendations during 2016–2019.Results. All patients have been discharged in satisfactory condition, with no intra-, postoperative complications or lethal outcomes.Discussion. Th e evidence presented displays feasibility of using the benchmark principles in laparoscopic adrenalectomy surgery. Laparoscopic adrenalectomy is superior in reducing the recovery time, surgical trauma, complication incidence, length of hospital stay, treatment cost, the improvement of overall wellbeing post-surgery and patients’ quality of life. Th ese principles proved effective to avoid intra- and postoperative complications of laparoscopic adrenalectomy and facilitated revamping of the operation technique in left -sided adrenalectomy.Conclusion. Th e benchmark principles of laparoscopic adrenalectomy enable the procedure higher efficacy and safety and require further implementation and long-term assessment of the outcome.